2018
DOI: 10.4269/ajtmh.17-0777
|View full text |Cite
|
Sign up to set email alerts
|

Management and Follow-up Practices of Children with Unclassified Fever in Rural Ethiopia: Experiences of Health Extension Workers and Caregivers

Abstract: Different health-care management guidelines by the World Health Organization exist to help health workers in resource-limited settings treat patients. However, for children with unclassified fever and no danger signs, management guidelines are less clear and follow-up recommendations differ. Both a "universal follow-up" for all children, irrespective of health status, and a "conditional follow-up" only for children whose fever persists are recommended in different guidelines. It is unclear how feasible and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The design and results of this trial are published elsewhere, as is the qualitative evaluation of HEW's and caregivers' perception of the recommendations. [25][26][27] For this study, 24 semistructured interviews were conducted with fathers who had at least one child aged 2-59 months presenting to the HEW with fever. Half of the interviews (n=12) were conducted in Halaba woreda, 8 in Boloso Sore and 4 in Damot Gale.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…The design and results of this trial are published elsewhere, as is the qualitative evaluation of HEW's and caregivers' perception of the recommendations. [25][26][27] For this study, 24 semistructured interviews were conducted with fathers who had at least one child aged 2-59 months presenting to the HEW with fever. Half of the interviews (n=12) were conducted in Halaba woreda, 8 in Boloso Sore and 4 in Damot Gale.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…Recent studies show that mRDT-negative patients with cough or difficult breathing complaints in Malawi had 16.8 times higher odds of antibiotic overtreatment than mRDT-positive patients [ 41 ]; in Burkina Faso and Uganda both community and health facility workers prescribed antimalarials to mRDT-negative patients if no other fever cause was identified, often due to parental pressure [ 41 , 42 ]. However, when clear case management instructions were provided, as in this study, and non-malaria fever was introduced as a diagnostic term, HEWs felt empowered to withhold medicines, while simultaneously reassuring caregivers that their child was cared for [ 22 ]. This finding is supported by the low number of children in our study who were taken to another provider and provided with secondary treatment after being enrolled by the HEW.…”
Section: Discussionmentioning
confidence: 99%
“…There are typically 2 HEWs assigned to a health post in a sub-district with a population of 3,000–5,000; they are supported by the Health Development Army, female volunteers who enhance community engagement and encourage use of maternal and newborn health services [ 21 ]. While IMNCI recommends conditional follow-up, HEWs and their supervisors report a range of other practices for children with unclassified fever, including universal follow-up advice, immediate referral to health centres, and treatment with antimalarial tablets [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reviewed studies suggested solutions pertinent to the barriers discussed above. Various health systems strengthening, and quality improvement interventions, have been recommended by many studies, ranging from enhanced demand creation to realizing a reliable and consumer-centered service delivery (20,33,36,39,40,42,45,49,54,59,61,64).…”
Section: Enablersmentioning
confidence: 99%
“…Maintaining a consistent supply of essential drugs, supplies and equipment (49,60), and ensuring a functional referral system (39) were among the speci c solutions suggested to realize quality service delivery to improving health outcomes. Some studies (20,36,40,42) also emphasized the critical role of building the capacity of the health workforce through training, supervision, and availing clinical guidelines and protocols. For instance, iCCM-trained workers provided good quality care (36), and the training of providers also resulted in higher client satisfaction (20).…”
Section: Enablersmentioning
confidence: 99%